Three roles of metaphor on the interactivist framework - Mustafa, Mohamad Radzi (Journal of Modern Languages, 2017)
Metaphor has been understood historically from the literary point of view (Ortony, t993; 2-3). However, this paper understands metaphor as specialized system activities of the brain (Bickhard 1998) that is manifested at three levels of representation. The term ’role’ is used to describe how it displays itself at each level of representation. Hence, it shall be proposed that three roles of metaphor underlie human cognitive processes: as a vehicle for categorisation, for comparison in illuminating understanding; and for creation of new knowledge. This paper sets out to argue for these three roles of metaphor. It is hoped that by redefining metaphor as system activities, this understanding will provide a ’natural’ explanation of language and behaviour from biology specifically, that of neurobiology.